To rewrite the equation \( y + 10 = 10(x - 8) \) in slope-intercept form, we need to solve for \( y \).
-
Start with the given equation: \[ y + 10 = 10(x - 8) \]
-
Distribute the \( 10 \) on the right side: \[ y + 10 = 10x - 80 \]
-
Subtract \( 10 \) from both sides to isolate \( y \): \[ y = 10x - 80 - 10 \]
-
Simplify: \[ y = 10x - 90 \]
Now the equation is in slope-intercept form, which is \( y = mx + b \), where \( m \) is the slope and \( b \) is the y-intercept. Here, the slope \( m \) is \( 10 \) and the y-intercept \( b \) is \( -90 \). So, the final result is: \[ y = 10x - 90 \]